Association between gastroesophageal reflux and bronchopulmonary dysplasia in preterm infants: a systematic review and meta-analysis - XinYi Yu; MengKe Sun; Yu Hu (Frontiers in Nutrition)
ObjectiveGastroesophageal reflux (GER) has emerged as a potential contributor to lung injury. This meta-analysis aimed to evaluate the association between GER and bronchopulmonary dysplasia (BPD) in preterm infants.MethodsA systematic literature search was conducted in PubMed, Embase, Web of Science, and Cochrane Library databases up to Oct 19, 2024. Studies assessing the association between BPD and GER in preterm infants were included. Random-effects models was used to calculate pooled risk ratios (RR) with 95% confidence intervals (CIs). Sensitivity analyses and subgroup analyses were performed to assess the robustness of the findings.ResultsSeven studies were included in the meta-analysis. The overall analysis revealed a non-significant association between GER and BPD (RR = 1.35, 95% CI = 0.91–2.01), but significant heterogeneity was observed across the studies (p < 0.001, I2 = 95.2%). The pooled RR ranged from 1.17 (95% CI = 0.79–1.74) to 1.51 (95% CI = 1.02–2.22) with each study omitted. Funnel plot analysis showed noticeable asymmetry, and Egger’s test confirmed potential publication bias (P > |t| = 0.076). Subgroup analysis revealed that GER diagnosed with clinical therapy or ICD-9 codes was significantly associated with BPD (RR = 1.72, 95% CI = 1.52–1.95 and RR = 2.70, 95% CI = 2.48–2.94, respectively). However, GER diagnosed by pH monitoring did not show a statistically significant association with BPD (RR = 0.86, 95% CI = 0.71–1.05).ConclusionPreterm infants with clinically diagnosed GER may face an elevated risk of developing BPD. GER diagnosed by pH monitoring was not associated with BPD.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/.